Control Technology of Support Stability in Thick Seam with Large Dip Angle Split-level Roadway - MAO Jinfeng, WANG Peng, YANG Changde, LI Jinbo (Meikuang Anquan, 2020)
The paper proposes the scheme of split-level which is for the problems of downslide of roadway and flying refuse and slice slope in pseudo-inclined working face of thick seam with large dip angle in Suhanghe Coal Mine. The instability mechanism of supports is analyzed by establishing a mechanical model of its stability, and it shows that the slope section plays a key control role in controlling the equipment sliding. It can effectively reduce the sliding trend of the supports and improve the stability of the supports. Through numerical simulation, the law of strata pressure in working face is analyzed. The stress release zone and tensile failure zone of working face roof are asymmetrically distributed, and the tensile failure zone corresponds to the collapse line. Based on the field measurement, the adaptability of the support is analyzed. The support can meet the demand of safe production. The strength of the working face is not symmetrical. The rock pressure in the middle of the working face is the strongest, the dynamic load coefficient is 1.66, followed by the upper part, and the lower part is relatively flat.